2010
DOI: 10.1007/s00253-010-2619-y
|View full text |Cite
|
Sign up to set email alerts
|

Fermentation characteristics of Dekkera bruxellensis strains

Abstract: The influence of pH, temperature and carbon source (glucose and maltose) on growth rate and ethanol yield of Dekkera bruxellensis was investigated using a full-factorial design. Growth rate and ethanol yield were lower on maltose than on glucose. In controlled oxygen-limited batch cultivations, the ethanol yield of the different combinations varied from 0.42 to 0.45 g (g glucose)(-1) and growth rates varied from 0.037 to 0.050 h(-1). The effect of temperature on growth rate and ethanol yield was negligible. It… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
105
2
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 95 publications
(120 citation statements)
references
References 33 publications
11
105
2
2
Order By: Relevance
“…␤-Glucosidases are well-known for their role in flavor development in beer and wine (74,75). Additionally, ␤-glucosidase has been shown to play a role in the fermentation of cellobiose by B. bruxellensis (76)(77)(78)(79). Interestingly, we found that ST05.12/22 did contain another ␤-glucosidase gene, which was also present in AWRI 1499 and CBS 2499.…”
Section: Discussionmentioning
confidence: 48%
“…␤-Glucosidases are well-known for their role in flavor development in beer and wine (74,75). Additionally, ␤-glucosidase has been shown to play a role in the fermentation of cellobiose by B. bruxellensis (76)(77)(78)(79). Interestingly, we found that ST05.12/22 did contain another ␤-glucosidase gene, which was also present in AWRI 1499 and CBS 2499.…”
Section: Discussionmentioning
confidence: 48%
“…In D. bruxellensis, inhibition of fermentative metabolism caused by a lack of oxygen is known as the Custers effect and is mainly caused by inefficient redox balance mechanisms (40); unfortunately, this effect has not yet been investigated in a systematic manner. This effect has been observed in several strains; however, these strains were cultivated under very different conditions, thus hampering a rigorous comparison of their different behaviors (7,17,19). Due to this effect, under oxygen-limited conditions, one would expect lower glucose consumption and ethanol production rates than those under aerobic conditions.…”
Section: Resultsmentioning
confidence: 95%
“…D. bruxellensis has been reported as being unable to use xylose, but several strains are able to metabolize cellobiose (17). All these metabolic features have led to the idea that D. bruxellensis could be used for ethanol production at the industrial level (11,18,19). An alternative approach to improving the industrial use of lignocellulosic feedstocks for second-generation biofuel production by fermentation is the isolation and characterization of novel yeast strains that possess natural resistance to several stress conditions (e.g., high osmotic pressure, acidic pH, the presence of inhibitors, and oxidative stress) that microorganisms encounter during industrial processes.…”
Section: Importancementioning
confidence: 99%
See 1 more Smart Citation
“…But in production of beer and sourdough it is a desirable member of microflora which plays a key role in the spontaneous fermentation and food flavor (Stender et al, 2001;Blomqvist et al, 2010). The yeast Geotrichum candidum which was identified in our study is appearing in the early stages of ripening on soft and semi-hard French cheeses.…”
Section: Resultsmentioning
confidence: 68%